Pomen vadbe in drugih komplementarnih rehabilitacijskih tehnik pri obravnavi tendinopatij komolca - Meke, Veronika (Šport (Ljubljana), 2023)
Due to their increasing prevalence, tendinopathies present a significant health and economic problem. Lateral epicondilitis (LE), or lateral elbow tendinopathy, is the most common tendinopathy of the upper limb. It markedly reduces work capacity and participation in sporting and recreational activities, and poses a considerable financial burden. Thus, an efficacious rehabilitation modality is needed. The scientific literature lists numerous methods employed in LE rehabilitation, although the evidence base has not yet established the single most efficacious rehabilitation modality. The multiple reasons for this encompass low quality of studies, inconsistencies in reporting on the used methods and modalities, and a great number of different rehabilitation modalities and their combinations, including the possibility of a spontaneous improvement of this type of degenerative injury. Despite these limitations, the most efficacious approach to LE rehabilitation seems to be multimodal therapy.
Keywords: komolec; medicinska rehabilitacija; šport; športne poškodbe; vadba